Use of Green Mussel Shell as a Desulfurizer in the Blending of Low Rank Coal-Biomass Briquette Combustion - Mahidin, Mahidin; Gani, Asri; Hani, M. Reza; Syukur, Muhammad; Hamdani, Hamdani; Khairil, Khairil; Rizal, Samsul; Hadi, Abdul; Mahlia, T.M.I. (UI Scholars Hub, 2016)
Calcium oxide-based material is available abundantly and naturally. A potential resource of that material comes from marine mollusk shell such as clams, scallops, mussels, oysters, winkles and nerites. The CaO-based material has exhibited a good performance as the desulfurizer or adsorbent in coal combustion in order to reduce SO2 emission. In this study, pulverized green mussel shell, without calcination, was utilized as the desulfurizer in the briquette produced from a mixture of low rank coal and palm kernel shell (PKS), also known as bio-briquette. The ratio of coal to PKS in the briquette was 90:10 (wt/wt). The influence of green mussel shell contents and combustion temperature were examined to prove the possible use of that material as a desulfurizer. The ratio of Ca to S (Ca = calcium content in desulfurizer; S = sulfur content in briquette) were fixed at 1:1, 1.25:1, 1.5:1, 1.75:1, and 2:1 (mole/mole). The burning (or desulfurization) temperature range was 300-500 °C; the reaction time was 720 seconds and the air flow rate was 1.2 L/min. The results showed that green mussel shell can be introduced as a desulfurizer in coal briquette or bio-briquette combustions. The desulfurization process using that desulfurizer exhibited the first order reaction and the highest average efficiency of 84.5%.